A simple technique for coplanar camera calibration - Sirisantisamrid, Kaset; Tirasesth, Kitti; Matsuura, Takenobu (My University, 2008)
This paper proposes a simple technique for camera calibration under assumption that a calibration pattern is on world coordinate system. The proposed method consists of two steps. In the first step, the intermediate parameters, lens distortion coefficients, principal point and the distances between sensors are computed by an iterative linear method. Then, the camera parameters are determined from the obtained intermediate parameters. In the experimental results, the proposed method gives the accurate and stable camera parameters for change rotation angles when compared with the conventional method.
Keywords: Camera parameters; Coplanar camera calibration; Intermediate parameters; Iterative linear method